Impact of pesticides usage - a case study of organochlorine compound levels in the blood serum of selected Malaysian population groups - Wong, Kien Keong (1980)
The extent with which pesticides have been used in Malaysia has rarely been studies. This paper examined the impact of pesticides usage in Malaysia. Data on pesticides application in the Muda Padi area indicated increasingly excessive usage of pesticides. A case study was presented to show the prevalence and persistence of organochlorine (OCL) pesticides in the human environment. Blood samples from three population groups were drawn, analysed for OCL compounds in Malaysian padi farmers, rubber workers and general population were much higher than those in similar categories in the U.S.A. These results indicate that we should examine seriously our pesticide practices, pesticides Act and the implementation of integrated Pest Management. Development efforts may suffer setbacks because of the damage to our ecosystem caused by our poor agricultural chemicals control and management.